Nondestructive thickness measuring method for ceramic electrolyte film of solid oxide battery
By scanning the green ceramic electrolyte image to obtain RGB color information and establish functional relationships, the high cost and accuracy of ceramic electrolyte film thickness detection of solid oxide battery ceramic electrolyte is solved, lossless and real-time online detection is achieved, and the accuracy of thickness control is improved.
Patent Information
- Application Number
- CN202411410749.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-02-07
AI Technical Summary
In the prior art, when detecting the thickness of ceramic electrolyte film of solid oxide batteries, there are problems such as high cost, reduced measurement accuracy and inability to realize real-time data acquisition, especially in high temperature or harsh environments.
By scanning the image of the green ceramic electrolyte, RGB color information is obtained, and a functional relationship between the RGB color information and the actual thickness value is established, so as to realize non-destructive detection and real-time online detection of the thickness of the ceramic electrolyte film.
The non-destructive detection and real-time online detection of the thickness of ceramic electrolytes in solid oxide batteries are realized, which improves the accuracy of thickness control during the preparation of YSZ electrolyte films, and has the characteristics of low cost, relatively accurate, simple and easy to operate.
Smart Images

Figure CN119394194A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a nondestructive thickness measurement method for a ceramic electrolyte film of a solid oxide battery, belonging to the technical field of solid oxide battery performance detection. Background Art
[0002] Solid Oxide Fuel Cells (SOFC) have a high fuel utilization rate and can directly convert chemical energy into electrical energy. They are efficient and environmentally friendly all-solid-state devices. SOFC can be divided into three types according to the different electrolyte conductive materials, namely oxygen ion conduction, proton conduction, and oxygen ion-proton co-conduction. At present, according to the different film-forming principles, the preparation technology of oxygen ion conductive electrolyte (YSZ) thin film can be roughly divided into the following three methods, namely ceramic powder method (such as tape casting, wet spraying, screen printing, etc.), chemical method (spray pyrolysis, chemical vapor deposition, sol-gel, etc.) and physical method (thermal spraying, pulsed laser deposition, vacuum sputtering, etc.). Among them, the ceramic powder method is low-cost and most suitable for industrial production. It has broad market prospects, but compared with physical methods such as vacuum sputtering deposition and plasma spraying technology, it has poor repeatability and cannot accurately control the consistency of thickness in the preparation process of different batches of ceramic electrolyte films.
[0003] In response to the above challenges, the mainstream method currently adopted is to add a monitoring and feedback control module to the ceramic electrolyte preparation process to perform real-time detection of the ceramic electrolyte thickness during the preparation process. When it is found that the real-time detected ceramic electrolyte thickness value does not meet expectations, the electrolyte preparation process is adjusted in time by adjusting equipment parameters, slurry systems, etc., to control the thickness of different batches of ceramic electrolytes prepared within the error range. However, online detection systems usually need to be equipped with high-precision thickness gauges, such as ultrasonic thickness gauges, laser thickness gauges, infrared thickness gauges, etc., which are not only expensive but also many existing technologies may reduce measurement accuracy under high temperature or harsh environments, and have limited detection capabilities for small changes in ceramic electrolyte film thickness. Most importantly, humidity, temperature and other environmental conditions can affect the measurement results, especially in the wet film state. At present, some measurement methods have limited applicability to different substrates and coating types and cannot achieve real-time data collection, making it difficult to adjust production parameters in real time.
[0004] Therefore, real-time online detection of ceramic electrolyte thickness and timely feedback are the bottlenecks that need to be broken through. Summary of the invention
[0005] Based on the problems existing in the prior art, the present invention provides a non-destructive thickness measurement method for a solid oxide battery ceramic electrolyte film.
[0006] The technical solution proposed by the present invention to solve the problems of the prior art is as follows:
[0007] A non-destructive thickness measurement method for a solid oxide battery ceramic electrolyte film comprises the following steps:
[0008] (1) preparing ceramic electrolyte green sheets with standard ceramic electrolyte films of different thicknesses on an anode substrate, scanning the ceramic electrolyte green sheets to obtain images thereof, and extracting RGB color information;
[0009] (2) sintering the ceramic electrolyte green body, and then obtaining its actual thickness value by scanning electron microscopy;
[0010] (3) Establishing the functional relationship between the RGB color information and the actual thickness value of the standard ceramic electrolyte film;
[0011] (4) A ceramic electrolyte green body of the ceramic electrolyte film to be tested is prepared on the anode substrate, the ceramic electrolyte green body is scanned, its image is acquired in real time, and RGB color information is extracted and substituted into the functional relationship of step (3) to obtain its real-time thickness.
[0012] Preferably, in step (1) and step (4), the ceramic electrolyte slurry is coated on the anode substrate and dried to obtain a ceramic electrolyte green body.
[0013] Preferably, in step (1) and step (4), the ceramic electrolyte green sheets of the standard ceramic electrolyte film and the ceramic electrolyte film to be tested are prepared by the same method, wherein the chemical composition of the electrolyte is the same.
[0014] Specifically, the ceramic electrolyte green body is prepared by screen printing, spraying, casting, drip coating, etc.
[0015] Preferably, in step (1) and step (4), the chemical composition of the anode substrate is the same and both are green (not pre-fired).
[0016] Preferably, in step (1) and step (4), the image is obtained by scanning with a printer, a high-speed industrial camera, etc.
[0017] Preferably, in step (1) and step (4), RGB color information is extracted using Photoshop software.
[0018] Preferably, the solid oxide battery includes but is not limited to a flat plate type.
[0019] Compared with the prior art, the advantages of the present invention are:
[0020] The present invention proposes for the first time a non-destructive thickness measurement method for a solid oxide battery ceramic electrolyte film. The actual thickness of the dense ceramic electrolyte film after sintering is detected by using the RGB color information in the scanning image of the ceramic electrolyte green body, thereby realizing non-destructive detection of the thickness of the solid oxide battery ceramic electrolyte and real-time online detection of the electrolyte thickness during the preparation process, thereby improving the accuracy of thickness control during the preparation of the YSZ electrolyte film. The method has the characteristics of low cost, high accuracy, and simple and easy operation. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a schematic diagram of the system structure and method flow.
[0022] Figure 2 Flow chart for preparing electrolyte films of different thicknesses by wet spraying.
[0023] Figure 3 (a1)~(a3), (b1)~(b3), (c1)~(c3), (d1)~(d3), and (e1)~(e3) are printer scan images, electrolyte film cross-section SEM and EDS images of Cell-1 battery, Cell-2 battery, Cell-3 battery, Cell-4 battery, and Cell-5 battery electrolyte green body, respectively.
[0024] Figure 4 The relationship curve between the RGB value of the electrolyte green body prepared by wet spraying and the thickness of the electrolyte film is (a) linear function; (b) quadratic function; (c) power function.
[0025] Figure 5 (a1) and (a2), (b1) and (b2), (c1) and (c2), (d1) and (d2), (e1) and (e2) are printer scanning images of the electrolyte green body and SEM images of the electrolyte film cross-section of Cell-A battery, Cell-B battery, Cell-C battery, Cell-D battery and Cell-E battery, respectively.
[0026] Figure 6 (a1) and (a2), (b1) and (b2), (c1) and (c2), (d1) and (d2), (e1) and (e2) are printer scanning images of the electrolyte green body and SEM images of the electrolyte film cross-section of Cell-SY-1 battery, Cell-SY-2 battery, Cell-SY-3 battery, Cell-SY-4 battery and Cell-SY-5 battery, respectively.
[0027] Figure 7 Curves showing the relationship between the RGB value of the electrolyte green body prepared by screen printing and the thickness of the electrolyte film (a) linear function; (b) quadratic function; (c) power function.
[0028] Figure 8 (a1) and (a2), (b1) and (b2) are the printer scanning images of the electrolyte green body of Cell-SY-A battery and Cell-SY-B battery and the SEM images of the cross-section of the electrolyte film, respectively.
[0029] Fig. 9 The difference between the measured value and the actual thickness of the ceramic electrolyte film prepared by wet spraying (a) and the ceramic electrolyte film prepared by screen printing (b). DETAILED DESCRIPTION
[0030] In order to better understand the technical content of the present invention, specific embodiments are given and described as follows in conjunction with the accompanying drawings.
[0031] Various aspects of the present invention are described with reference to the accompanying drawings in the present invention, in which many illustrative embodiments are shown. Embodiments of the present invention need not be defined to include all aspects of the present invention. It should be understood that the various concepts and embodiments introduced above, as well as those described in more detail below, can be implemented in any of many ways, because the concepts and embodiments disclosed by the present invention are not limited to any implementation. In addition, some aspects disclosed by the present invention can be used alone, or used in any appropriate combination with other aspects disclosed by the present invention.
[0032] Combination Figure 1 The present invention proposes a non-destructive thickness measurement method for ceramic electrolyte film of solid oxide battery - a functional relationship is established based on the RGB color information in the image after the ceramic electrolyte is formed and the actual thickness value of the ceramic electrolyte after sintering obtained by scanning electron microscope, and the actual thickness of electrolytes of different thicknesses prepared under the same system is judged by the function. At the same time, a complete monitoring feedback system can be formed by combining machine learning and image recognition system, and the color information of the prepared electrolyte film can be monitored in real time during the production process to detect the thickness of the ceramic electrolyte film and compare it with the target value, automatically adjust the electrolyte preparation parameters, and realize accurate control of the electrolyte thickness, so that the film thickness is always kept within the set range. Finally, the integrity of the database and the accuracy of the detection are continuously improved through continuous detection and verification, and the detection model is optimized. This method can determine the thickness distribution of large-size solid oxide fuel cell electrolytes during preparation. This method detects through the functional relationship between the RGB color information of the electrolyte film image and the actual thickness value, with low cost and detection error within 0.5μm. This method can realize non-destructive detection of the thickness of ceramic electrolytes of solid oxide batteries and realize real-time online detection of electrolyte thickness during the preparation of solid oxide batteries.
[0033] Example 1 Detection of thickness of different electrolyte films prepared by wet spraying
[0034] The anode substrate is composed of an anode support and a functional layer, wherein the anode support and the functional layer are NiO-YSZ (NiO-Zr 0.84 Y 0.16 O 2-δ ), the electrolyte is YSZ (Zr 0.84 Y 0.16 O 2-δ ), and its half-cell structure is NiO-YSZ||YSZ. Anode-supported half-cells with different electrolyte thicknesses were prepared and named Cell-1, Cell-2, Cell-3, Cell-4, and Cell-5.
[0035] Wipe the surfaces of 5 unfired anode substrates clean with non-woven fabric and fix them. Use a PS-289 spray gun (0.3mm diameter) and air as the carrier gas for spraying, and the spraying pressure is set to 0.1MPa. Fill the spray pot with the ultrasonically dispersed electrolyte slurry, adjust the spraying distance to 9cm, and spray the YSZ slurry evenly on the anode substrate, repeatedly until a uniform white film appears on the anode substrate. Spray the YSZ electrolyte slurry on 5 unfired anode substrates respectively. After drying for 24 hours, 5 ceramic electrolyte green bodies with different thicknesses are obtained. The process is as follows: Figure 2 .
[0036] The ceramic electrolyte green body is image scanned and RGB color information is extracted. The process of extracting the RGB color information is as follows: placing the sample on a printer scanning module, using a printer with a model of HP Smart Tank 580-590 to scan the surface of the ceramic electrolyte green body, using HP Scan as the scanning software, with a scanning accuracy of 1200ppi, a scanning mode of color, and exposure setting parameters of 0, to obtain a JPEG format scanned image, importing the image into Photoshop software, using a color picker to pick up its RGB value, using the RGB average value of 31×31 pixels when picking points, and randomly taking 5 times of the same sample to calculate the average value, so as to determine the final RGB value.
[0037] After scanning, the five types of ceramic electrolyte green bodies were calcined at 1400°C for 5 hours to form dense ceramic electrolyte films, and SEM and EDS characterizations were performed to determine the actual thickness of the ceramic electrolyte films. The printer scanned images of the battery electrolyte green bodies, the SEM and EDS images of the electrolyte film cross-sections are shown in Figure 2. Figure 3 shown.
[0038] As shown in Table 1, the functional relationship between the RGB color information of the electrolyte film image and the actual thickness value is established, such as Figure 4 As shown in the figure, linear function, quadratic function and power function are used for fitting respectively, and the R2 To judge the fitting degree of the curve, select the function with the best fitting degree to establish the detection model. Figure 4 It can be seen that the fitting degree obtained by using the power function is the best.
[0039] Finally, the actual thickness of the electrolyte ceramic film to be tested prepared in the same system is detected through this functional relationship.
[0040] Through a wet spraying process, half-cells with 5 random electrolyte thicknesses were prepared using an unprefired anode substrate of the same composition and an electrolyte slurry of the same composition, and they were named Cell-A, Cell-B, Cell-C, Cell-D, and Cell-E, respectively. The same steps as above were used to scan the surfaces of the ceramic electrolyte green bodies of the half-cells with 5 random electrolyte thicknesses, and the RGB color information in the scanned image was extracted. The power function obtained above was used for detection, and the electrolyte thicknesses detected by the R value, G value, and B value were calculated, and the average value was obtained to obtain the thickness detection value of the ceramic electrolyte film to be tested.
[0041] The test results were verified by SEM characterization of the ceramic electrolyte green bodies of the above five random thickness electrolyte half-cells after calcination at 1400 °C for 5 h. Figure 5 The actual thickness value shown is compared with the detected value to calculate the detection error. The results are shown in Table 3. It can be seen that the detection errors of the five electrolyte thicknesses are all within 0.5μm. Feeding these five sets of data back to the database can further optimize the function fit. The detection errors of different functional relationships are shown in Table 3. Fig. 9 As shown in (a) in the figure, it can be seen that the detection accuracy can be significantly improved by correctly selecting the functional relationship.
[0042] Example 2 Detection of thickness of different electrolyte films prepared by screen printing
[0043] The anode substrate is composed of an anode support and a functional layer, wherein the anode support and the functional layer are NiO-YSZ (NiO-Zr 0.84 Y 0.16 O 2-δ ), the electrolyte is YSZ (Zr 0.84 Y 0.16 O 2-δ ), and its half-cell structure is NiO-YSZ||YSZ. Anode-supported half-cells with different electrolyte thicknesses were prepared by screen printing at different times, and were named Cell-SY-1, Cell-SY-2, Cell-SY-3, Cell-SY-4, and Cell-SY-5. After drying for 24 hours, 5 standard ceramic electrolyte green sheets with different thicknesses were obtained. The printer scanned images of the above battery electrolyte green sheets and the SEM cross-section of the electrolyte film are shown in Figure 2. Figure 6 As shown in Table 2, a functional relationship between the RGB color information of the above-mentioned battery standard electrolyte green body image and the actual thickness value is established. The battery to be tested is a half-cell with two random thickness electrolytes, named Cell-SY-A and Cell-SY-B respectively. The remaining steps are the same as those in Example 1 and will not be repeated here.
[0044] Finally, combine Figure 7 , a quadratic function is selected to detect the actual thickness of the electrolyte ceramic film to be tested prepared under the same system. The test results are shown in Table 4. The actual thickness value is Figure 8 As shown in Figure 2, it can be seen that the detection errors of the five electrolyte thicknesses are all within 0.5 μm. The detection errors of different functional relationships are shown in Figure 2. Fig. 9 As shown in (b) in the figure, for the screen printing system, the difference between different electrolyte thicknesses is even greater, but the accuracy of detection can also be significantly improved by correctly selecting the functional relationship, which once again verifies the practical feasibility of this method.
[0045] Table 1 Database of electrolyte green bodies prepared by wet spraying
[0046]
[0047] Table 2 Screen printing electrolyte green body database
[0048]
[0049] Table 3 Wet spraying electrolyte thickness detection model and verification data
[0050]
[0051]
[0052] Table 4 Screen printing electrolyte thickness detection model and verification data
[0053]
[0054] Although the present invention has been disclosed as above with preferred embodiments, it is not intended to limit the present invention. A person with ordinary knowledge in the technical field to which the present invention belongs may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be determined by the definition of the claims.
Claims
1. A non-destructive thickness measurement method for solid oxide battery ceramic electrolyte film, characterized in that: The steps include: (1) preparing ceramic electrolyte green sheets with standard ceramic electrolyte films of different thicknesses on an anode substrate, scanning the ceramic electrolyte green sheets, acquiring images thereof, and extracting RGB color information; (2) sintering the ceramic electrolyte green body, and then obtaining its actual thickness value by scanning electron microscopy; (3) Establish the functional relationship between the RGB color information and the actual thickness value of the standard ceramic electrolyte film; (4) A ceramic electrolyte green body of the ceramic electrolyte film to be tested is prepared on the anode substrate, the ceramic electrolyte green body is scanned, its image is acquired in real time, and RGB color information is extracted and substituted into the functional relationship of step (3) to obtain its real-time thickness.
2. The method according to claim 1, characterized in that In step (1) and step (4), the ceramic electrolyte slurry is coated on the anode substrate and dried to obtain a ceramic electrolyte green body.
3. The method according to claim 1, characterized in that In step (1) and step (4), the ceramic electrolyte green sheets of the standard ceramic electrolyte film and the ceramic electrolyte film to be tested are prepared by the same method, wherein the chemical composition of the electrolyte is the same.
4. The method according to claim 1 or 3, characterized in that The ceramic electrolyte green body is prepared by screen printing, spraying, casting or drip coating.
5. The method according to claim 1, characterized in that In step (1) and step (4), the chemical composition of the anode substrate is the same.
6. The method according to claim 1, characterized in that In step (1) and step (4), the image is obtained by scanning with a printer or a high-speed industrial camera.
7. The method according to claim 1, characterized in that In step (1) and step (4), RGB color information is extracted by color extraction software.
8. The method according to claim 1, characterized in that The solid oxide cell is of flat plate type or tubular type.